Immersive robotics experiments - Telexistence PhD (videos) - Mazeas, Damien (Cranfield University, 2023)
This page contains a list of videos illustrating some of the experiments carried out during Mr. Mazeas's thesis on telexistence.
Keywords: 'teleoperation'; 'virtual reality'; 'fanuc'; 'industrial arm'; '3D'; 'remote control'; 'human interfacing'; 'immersive rebotics'; 'UR16e'; 'Universal Robot'; 'inverse kinematics'; 'DDS'; 'Distributed Systems'; 'Unity'; 'Telexistence'; 'Telepresence'; 'presence'; 'immersion'; 'robots'